Anterior Cervical Discectomy With Fusion Using a Local Source for Cancellous Autograft: A Biomechanical Analysis of Vertebral Body Stability in an Osteopenic Bone Model. (September 2017) - Walterscheid, Zakk; O'Neill, Conor; Ochs, Alex; D'Averso, Adrian; Dew, Christopher; Huntington, Alyssa; Ma, Grace; Behrend, Caleb; De Vita, Rafaella; Carmouche, Jonathan
Background: Anterior cervical discectomy with fusion is an effective treatment for patients having cervical radiculopathy and myelopathy. To reduce morbidity associated with autograft taken from the iliac crest without sacrificing high fusion rates, a novel technique that harvests bone from the vertebral body adjacent to the operative disc space has been proposed. The effects of square and round bone graft harvest techniques on the mechanical stability of the osteopenic donor vertebrae are unknown. We analyzed the biomechanical implications of the technique by subjecting osteopenic models to uniaxial compression to compare yield strengths of surgically altered and unaltered specimens. Methods: Biomechanical grade polyurethane foam was cut into 60 different 12 mm × 17 mm × 20 mm blocks. The foam had a density of 10 pounds per cubic foot, simulating osteoporotic bone. Rectangular prism (4 mm × 4 mm × 6 mm) and cylindrical cores ( r = 2 mm, h = 8 mm) were removed from 20 blocks per group. Twenty samples were left intact as a control group. Anterior plate screws were applied to the models and a Polyether ether ketone (PEEK) interbody spacer was placed on top. Samples underwent uniaxial compression at 0.1 mm/s until mechanical failure. Points of structural failure were determined using a 0.1% offset on a force–displacement curve and compared to determine the reductions in compressive strength. Results: The mean force eliciting structural failure for intact samples was 450.6 N. Average failure forces for rectangular prisms and cylindrical cores removed were 383.2 and 395.4 N, respectively. Removal of a rectangular prismatic core of the necessary volume resulted in a 15.0% reduction in compressive strength, while removal of a cylindrical core of comparable volume facilitated a reduction of 12.2%. Conclusion: Local autograft harvested from adjacent vertebrae reduces morbidity associated with a second surgical site while minimally reducing the compressive strength of the donor vertebra in an osteopenic model, lending credence to the efficacy of this technique in elderly patient populations.